2, 4‐Dinitrophenol‐Catalyzed α‐C(sp3)−H and C(sp)−H Bond Functionalization of Cyclic Amines and Alkynes: Highly Regio‐/Diastereoselective Synthesis of α‐Alkynyl‐3‐Amino‐2‐Oxindoles. Issue 29 (10th June 2016) - Kumar, Mukesh; Kaur, Banni P.; Chimni, Swapandeep S
Abstract: A transition‐metal‐ and oxidant‐free DNP (2, 4‐dinitrophenol)‐catalyzed atom‐economical regio‐ and diastereoselective synthesis of monofunctionalized α‐alkynyl‐3‐amino‐2‐oxindole derivatives by C−H bond functionalization of cyclic amines and alkynes with indoline‐2, 3‐diones has been developed. This cascade event sequentially involves the reductive amination of indoline‐2, 3‐dione by imine formation and cross coupling between C(sp 3 )−H and C(sp)−H of the cyclic amines and alkynes. This reaction offers an efficient and attractive pathway to different types of α‐alkynyl‐3‐amino‐2‐oxindole derivatives in good yields with a wide tolerance of functional groups. The salient feature of this methodology is that it completely suppresses the homocoupling of alkynes. To the best of our knowledge, this is the first example of a DNP‐catalyzed metal‐free direct C(sp 3 )−H and C(sp)−H bond functionalization providing biologically active α‐alkynyl‐3‐amino‐2‐oxindole scaffolds. Abstract : Less is more : A transition‐metal‐ and oxidant‐free DNP (2, 4‐dinitrophenol)‐catalyzed regio‐ and diastereoselective synthesis of monofunctionalized α‐alkynyl‐3‐amino‐2‐oxindoles by C−H bond functionalization of cyclic amines and alkynes with indoline‐2, 3‐diones has been developed. This method completely suppresses the homocoupling of alkynes.